Suicide prevention curriculum development for health and social care students: A scoping review - Clíodhna O’ Brien; Kerrie Gallagher; Michelle O’ Driscoll; Doireann Ní Dhálaigh; Paul Corcoran; Mette Valdersdorf Jensen; Eve Griffin (PLoS ONE, 2025)
Background Suicide is a widely recognised public health concern. International evidence indicates that many individuals who die by suicide have had contact with a healthcare professional in the year preceding their death. Moreover, the evidence regarding the training of healthcare professionals is concerning and points to gaps in the provision of training to adequately prepare health professionals in responding to and assisting individuals in a state of suicidal crisis. There is a recognised opportunity to ensure that all health and social care students, regardless of their discipline, receive formal suicide prevention training. Despite this imperative need, there is a notable absence of literature summarising the current state of such training across healthcare disciplines. This scoping review aimed to identify literature describing the design, development, implementation, and/or evaluation of suicide prevention training for healthcare and/or social care students in higher education settings. Methods Following a predetermined protocol, we conducted a scoping review adhering to PRISMA guidelines for Scoping Reviews (PRISMA-ScR). The author team formulated a search strategy incorporating variations of keywords such as “student,” “suicide prevention,” and “education.” The search spanned six databases—PubMed, ERIC (Education Resources Information Center), CINAHL, Embase, PsycInfo (EBSCO), and Web of Science. Additionally, grey literature sources were explored, alongside forward and backward citation searches of the included articles. Two reviewers independently carried out title and abstract screening, as well as full-text screening. Data extraction from the included studies was also conducted independently by two reviewers, with any discrepancies resolved through group consensus. A narrative summary of key findings was developed. Results In total 58 articles were included which detailed several programmes conducted mostly in the United States of America and Australia and were targeted at a variety of healthcare students. When specified, learning outcomes were associated with improving attitudes and developing knowledge. The programmes employed diverse teaching strategies, including lectures, role-playing, and patient simulations. While student evaluations generally showed improvements in knowledge, confidence, and preparedness, the evidence on the effectiveness of different instructional approaches remains inconsistent. Conclusion By integrating comprehensive suicide prevention training into health and social care curricula, there is an opportunity to instil the knowledge, skills, and attitudes necessary to effectively address suicide risk. Further research is warranted to elucidate the most effective delivery methods and teaching modalities for suicide prevention training programmes in health and social care students, with scope for further exploration of interprofessional learning opportunities in this area. The development of internationally recognised core competencies and learning outcomes for health and social care students in this area is also critical to ensure a consistent, effective approach to suicide prevention across healthcare and social care settings.